Twins - Johnson, Varian 1977- (Graphix, an imprint of Scholastic, 2020)
"Maureen and Francine Carter are twins and best friends. They participate in the same clubs, enjoy the same foods, and are partners on all their school projects. But just before the girls start sixth grade, Francine becomes Fran -- a girl who wants to join the chorus, run for class president, and dress in fashionable outfits that set her apart from Maureen. A girl who seems happy to share only two classes with her sister! Maureen and Francine are growing apart and there's nothing Maureen can do to stop it. Are sisters really forever? Or will middle school change things for good?"--Provided by publisher
Keywords: Gruppenkohäsion; Zwilling; Schwarze; Individualität; Erwachsenwerden; Freundschaft; Engagement; Rivalität; Schule; Selbstbewusstsein; USA; Twin sisters / Comic books, strips, etc; Twin sisters / Juvenile fiction; African American girls / Comic books, strips, etc; African American girls / Juvenile fiction; Sibling rivalry / Comic books, strips, etc; Sibling rivalry / Juvenile fiction; Middle schools / Comic books, strips, etc; Middle schools / Juvenile fiction; Maturation (Psychology) / Comic books, strips, etc; Maturation (Psychology) / Juvenile fiction; Twins / Fiction; Individuality / Fiction; Identity (Psychology) / Fiction; JUVENILE FICTION / Comics & Graphic Novels / General; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / People & Places / United States / African American; Twin sisters; African American girls; Maturation (Psychology); Middle schools; Sibling rivalry; Sisters; Twins; Twins / Comic books, strips, etc; Identity (Psychology) / Comic books, strips, etc; Graphic novels; Domestic comics; Coming-of-age comics; Comics (Graphic works); Bildungsromans; Fiction; Juvenile works; Comic